Fields of Gold - Fairbairn, Madeleine (Cornell University Press, 2023)
Fields of Gold critically examines the history, ideas, and political struggles surrounding the financialization of farmland. In particular, Madeleine Fairbairn focuses on developments in two of the most popular investment locations, the US and Brazil, looking at the implications of financiers' acquisition of land and control over resources for rural livelihoods and economic justice. At the heart of Fields of Gold is a tension between efforts to transform farmland into a new financial asset class, and land's physical and social properties, which frequently obstruct that transformation. But what makes the book unique among the growing body of work on the global land grab is Fairbairn's interest in those acquiring land, rather than those affected by land acquisitions. Fairbairn's work sheds ethnographic light on the actors and relationships—from Iowa to Manhattan to São Paulo—that have helped to turn land into an attractive financial asset class. Thanks to generous funding from UC Santa Cruz, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other repositories.